Medial Meniscal Allograft Transplantation: The Bone Plug Technique - Chase S. Dean, M.D. (Arthroscopy Techniques, 2016)
The medial meniscus is crucial for knee homeostasis. Treating patients who have undergone a subtotal or total meniscectomy, or equivalent irreparable tear pattern, can be extremely challenging, especially in young, active patients. The importance of meniscal preservation has been reported by several authors. Meniscal repair is now widely accepted as the first surgical option for treating medial meniscal tears. Moreover, current guidelines recommend preserving as much meniscal tissue as possible. Treating a symptomatic medial meniscectomized knee is challenging because of limited surgical options. In this context, medial meniscal allograft transplantation arises as the preferred procedure. The purpose of this article was to detail the arthroscopic medial meniscal allograft transplantation technique with the use of 2 bone plugs.